Good Firms, Worker Flows and Local Productivity - Michel Serafinelli (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
A consensus has emerged that agglomeration economies are an important factor explaining why firms cluster next to each other. Yet disagreement remains over the sources of these agglomeration effects, given non-trivial measurement challenges. This paper is the first to present direct evidence showing how localized knowledge spillovers arise from workers changing jobs within the same local labor market. Specifically, I as-sess the extent to which firm-to-firm labor mobility enhances the productivity of firms located near highly productive firms, using a unique dataset combining Social Security earnings records and balance sheet information for Veneto, a region of Italy with many successful industrial clusters. I first identify a set of highly productive firms, then show that hiring workers with experience at these firms significantly increases the productivity of other firms. To address identification threats, primarily due to unobservable firm-level productivity shocks correlated with hiring, I use a novel instrumental vari- able strategy, which exploits downsizing events at highly productive firms, in addition to control function methods in the spirit of the productivity literature. My findings from both approaches imply that worker flows can explain around 10 percent of the productivity gains experienced by other firms when new highly productive firms are added to a local labor market.
Keywords: R10; D24; J31; 330